Scientific Methods for Preserving Archaeological Metal Artifacts in Egyptian Museum Environments. (Journal of Nuclear Technology in Applied Science, 2024)
This research studied the significance of protecting metal artifacts in museums due to their cultural value and the challenges they face from environmental and chemical factors that cause deterioration. Types of Metal Artifacts include gold, silver, copper, bronze, iron, electrum, and platinum, each metal has different levels of resistance to corrosion. Gold and platinum were more resistant, while copper, bronze, and iron are more prone to rust and patina formation. Factors affecting deterioration include humidity, temperature, air pollutants, human contact, light (especially UV) and biological factors like microorganisms, all of them cause oxidation, corrosion, and surface damage. Preservation Methods involve controlling the environment (humidity, temperature), using protective packaging and coatings, ensuring safe display conditions, and performing regular inspections with advanced technologies like microscopes and X-rays. Cleaning techniques range from mechanical and laser cleaning to careful chemical treatments to remove dirty spots, rust, and corrosion without damaging the artifacts. Modern protective methods include Nano coatings, ultrasonic cleaning, and electronic devices like X-rays to assess and treat corrosion.
Keywords: Metal; Museum; corrosion; Artificial Intelligence